A switching action model for DEM-based multi-agent crowded behavior simulator. (November 2015) - Harada, Eiji; Gotoh, Hitoshi; Abd Rahman, Noorhazlinda Binti
Highlights: The switching action model is developed to simulate change in destination. The switching action model is based on the convolution integral of two functions. Appropriate switching action behavior and contact forces in crowd are monitored. Abstract: When the number of evacuees exceeds a capacity of an evacuation area, people who cannot enter the evacuation area have to change in his/her destination to go another area. To simulate the change in destination, a switching action model is developed. The behavior of change in destination during evacuation will be considered as a significant factor. Previously the authors have developed a microscopic multi-agent model based on the Distinct Element Method (DEM). In this paper, the switching action algorithm is introduced into our conventional DEM-based multi-agent model so that the change in destination during evacuation can be reproduced. The new formulation of the switching action model is based on the convolution integral of two functions. Currently, the newly developed model is validated by means of sensitivity analysis in which several values of model parameter have been tested. Accordingly, appropriate switching action behavior and contact force acting on each person are monitored. The proposed model is then demonstrated on different conjectural scenarios of the evacuation process.